2015
DOI: 10.1016/j.jpha.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple responses optimization in the development of a headspace gas chromatography method for the determination of residual solvents in pharmaceuticals

Abstract: An efficient generic static headspace gas chromatography (HSGC) method was developed, optimized and validated for the routine determination of several residual solvents (RS) in drug substance, using a strategy with two sets of calibration. Dimethylsulfoxide (DMSO) was selected as the sample diluent and internal standards were used to minimize signal variations due to the preparative step. A gas chromatograph from Agilent Model 6890 equipped with flame ionization detector (FID) and a DB-624 (30 m×0.53 mm i.d., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The retention of polar solvents on a DB-624 column is relatively stronger at high temperatures and could provide high separation between solvents which has minor differences in boiling points. Since the objective was to develop an efficient HSGC method, a DB-624 column (30 m × 0.53 mm, 3.0 µm film thickness) was selected, which is commonly used for residual solvent determination [26][27][28][29]. As shown in Fig.…”
Section: Selection Of Columnmentioning
confidence: 99%
“…The retention of polar solvents on a DB-624 column is relatively stronger at high temperatures and could provide high separation between solvents which has minor differences in boiling points. Since the objective was to develop an efficient HSGC method, a DB-624 column (30 m × 0.53 mm, 3.0 µm film thickness) was selected, which is commonly used for residual solvent determination [26][27][28][29]. As shown in Fig.…”
Section: Selection Of Columnmentioning
confidence: 99%
“…Previous work in this area concentrated on BC or BC composites rather than RBC and no relevant study on the issue of residual solvent/ions produced during the process of BC regeneration has been reported. Residual solvents (RS) and residual ions (RI) may represent a potential risk for human health due to their toxicity and their undesirable side effects [23] and they should be removed through some form of effective post-treatment. Hence, for the first time, an attempt was made to detect RS in RBC filaments using gas chromatography-mass spectrometry (GC-MS) and Inductively Coupled Plasma Emission Spectrometry (ICP-MS) was utilizes to measure the amount of RI.…”
Section: Figmentioning
confidence: 99%
“…As residual solvents (RS) and residual ions (RI) may represent a potential risk for human health due to their toxicity and their undesirable side effects [33], an attempt was made to detect residuals, especially lithium ions in the RBC/BC filaments. It has been reported that lithium can either inhibit or stimulate growth of normal [34,35] and cancer cells [36,37] and has dose-dependent effects [38].…”
Section: Detection Of Residual Solventmentioning
confidence: 99%
“…RSM is a collection of systematic research widely applied in different disciplines, including chemistry, biology, engineering and others. 17 It includes statistical methods to analyse the recorded data of response variables together with designed factors and to carry out optimization after parametric surrogate models are generated. 17 Although the mathematical results of RSM may lack physical significance, they are statistically significant and more precise than manual comparison work in trend description and prediction.…”
Section: Introductionmentioning
confidence: 99%
“…17 It includes statistical methods to analyse the recorded data of response variables together with designed factors and to carry out optimization after parametric surrogate models are generated. 17 Although the mathematical results of RSM may lack physical significance, they are statistically significant and more precise than manual comparison work in trend description and prediction. 18 Moreover, this approach has been found to be effective for obtaining optimal solutions predicted for the whole range of optimal goal settings instead of being chosen from limited experiments.…”
Section: Introductionmentioning
confidence: 99%